Voltage mapping model based short-circuit fault location method in distribution network with DG - Zhihua Zhang; Duhao Song; Hongjie Wu; Yuxiao Xing; Yongtao Tian; Bingyin Xu; Yongliang Liang (International Journal of Electrical Power & Energy Systems)
With the rapid development of smart grid, low-voltage detection data is becoming increasingly abundant. However, the data utilization is not deep enough. In this paper, a method for fault location of medium-voltage side based on low-voltage monitoring information is proposed. Firstly, the mapping model of low-voltage side phase-to-phase voltage amplitude and medium-voltage side voltage phasor is deduced, when short-circuit fault occurs. Then, according to the distribution characteristics of voltage and current phasor information calculated on the medium-voltage side, short-circuit fault section location and fault distance measurement method is presented separately. Meanwhile, the implementation process for the fault location method is given and the influence factor is analyzed. Finally, IEEE 33 nodes distribution network simulation model is constructed by PSCAD/EMTDC. The simulation results verify the accuracy of the voltage mapping model and the effectiveness of the location method. It provides a new approach for the in-depth utilization of low-voltage monitoring information.